2015
DOI: 10.1038/srep13654
|View full text |Cite
|
Sign up to set email alerts
|

EXTL2 and EXTL3 inhibition with siRNAs as a promising substrate reduction therapy for Sanfilippo C syndrome

Abstract: Sanfilippo syndrome is a rare lysosomal storage disorder caused by an impaired degradation of heparan sulfate (HS). It presents severe and progressive neurodegeneration and currently there is no effective treatment. Substrate reduction therapy (SRT) may be a useful option for neurological disorders of this kind, and several approaches have been tested to date. Here we use different siRNAs targeting EXTL2 and EXTL3 genes, which are important for HS synthesis, as SRT in Sanfilippo C patients’ fibroblasts in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 9 publications
2
29
1
Order By: Relevance
“…In Sanfilippo disease (mucopolysaccharidosis III), there is an accumulation of heparan sulfate in the lysosomes due to an impaired function of one of several lysosomal enzymes. We have assayed the inhibition of the EXTL2 and EXTL3 genes, as a substrate reduction therapy for Sanfilippo C disease in patients' fibroblasts and we are currently performing a similar approach on Sanfilippo C neurons, derived from induced pluripotent stem cells (iPSC) generated by our group …”
Section: Osteochondromatosis or Multiple Hereditary Exostosismentioning
confidence: 99%
“…In Sanfilippo disease (mucopolysaccharidosis III), there is an accumulation of heparan sulfate in the lysosomes due to an impaired function of one of several lysosomal enzymes. We have assayed the inhibition of the EXTL2 and EXTL3 genes, as a substrate reduction therapy for Sanfilippo C disease in patients' fibroblasts and we are currently performing a similar approach on Sanfilippo C neurons, derived from induced pluripotent stem cells (iPSC) generated by our group …”
Section: Osteochondromatosis or Multiple Hereditary Exostosismentioning
confidence: 99%
“…XYLT1, XYLT2, GALTI, and GALTII [49]), as well as enzymes specific to HS chain elongation (e.g. EXTL2 and EXTL3 [50,51]). These studies together demonstrated decrease in the targeted mRNA concomitant with reduced GAG biosynthesis and attenuated phenotypes in MPS I and III patient fibroblasts.…”
Section: Glycosaminoglycanmentioning
confidence: 99%
“…A different SRT approach consists in the use of RNA interference (RNAi) to inhibit genes responsible for GAG synthesis. Patients' fibroblasts treated with siRNAs or shRNAs against two genes involved in HS synthesis showed a clear reduction in GAG production [23][24][25] and HS storage [25]. However, given the neurological symptoms seen in patients, it is crucial to study SRT in relevant human neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…Here we combined these three iPSC lines with optimized protocols to obtain neurons [31] and astrocytes [32], creating novel and relevant disease models that recapitulate major Sanfilippo syndrome hallmarks. We then assayed an siRNA-based SRT strategy that was successful in treating patient fibroblasts [25] and showed that this strategy is not effective in neural cells, highlighting the importance of using disease-relevant cells in studies of disease mechanisms and drug screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation